PENGARUH AUDIT TENURE, ROTASI AUDIT, UKURAN KAP DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Endang Sri Mulatsih; Winda Feriyana (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of audit tenure, audit rotation, KAP size and audit committee on audit quality. Audit quality is measured by a dummy variable, namely using the average ROA. The population of this study are all Manufacturing Companies in the Basic Industry and Chemical Sector which are listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Sampling technique with purposive sampling method. The analysis technique uses logistic regression. The results of this study show that tenure audits have a positive effect on audit quality. Audit rotation has a negative effect on audit quality. KAP size and audit committee have no effect on audit quality. Keyword : Tenure Audit, Audit Rotation, Size KAP, Audit Comitte and Audit Quality